ANALISIS OVERALL EQUIPMENT EFFECTIVENESS (OEE) PADA MESIN CNC CUTTING - Hidayat Hidayat; Moh. Jufriyanto; Akhmad Wasiur Rizqi (ROTOR, 2020)
PT PAL Indonesia (Persero) is one of the state-owned industries and manufactures engaged in the maritime sector. This company has production equipment complete enough to carry out its production of ship components. There is a problem in this machine, it can be seen by the frequency of damage that occurs to machines or equipment due to the damage so that the production target is sometimes not achieved. Another consequence caused by damage to machines or equipment is in terms of the quality of the resulting product, where products that do not comply with quality standards will be reprocessed. Increasing production efficiency at this company is to measure the effectiveness of CNC Cutting machines using the OEE (Overall Equipment Effectiveness) method. The results of this study suggest that the company should pay more attention to factors of use of production time, work according to standards, operator knowledge, and maintenance of machines. By paying attention to these factors, it is expected that the company's productivity will increase and the production process will run effectively and efficiently.